Study of the Treatment of Kidney Stone with Upupa Epops, Cissus Adanta Roxb and Cissus Javana DC in the Urinary Medium: A Comparative Approach - S. O. Ibopishak; D. A. Bimola (Challenges and Advances in Chemical Science Vol. 3, 2021)
Kidney stone is a very common disease suffered by many peoples. It causes health problems such as severe pain, urinary obstruction and infection that adversely affect well being individuals. It may be treated by using allopathic and herbal drugs, lithotripsy, open surgery etc. Medicinal plants are also used for such treatment. These plants are less side effect and more economic. In this article, chemoinhibitory effects of Upupa epops, Cissus adnata Roxb and Cissus javana DC for calcium phosphate(CP) stone and calcium oxalate(CaOX) stone formation in the aqueous and urinary media is studied. Kidney stone is treated with Hoopoe, Cissus adnata Roxb and Cissus javana DC in the urinary medium. The comparative study shows the inhibitory effect of the mixture of Hoopoe and Cissus javana DC for CP and CaOX stones in the aqueous and urinary media is higher and also the digestion or dissolution of kidney stone is higher by this mixture in the urinary medium.